2018
DOI: 10.1016/j.scienta.2018.04.059
|View full text |Cite
|
Sign up to set email alerts
|

Effect of olive trees density on the quality and composition of olive oil from cv. Arbequina

Abstract: A B S T R A C TThe number of plants per hectare is a key factor for olive tree productivity. Nevertheless, information about the effect of tree density on olive oil quality and composition is scarce. Thus, the effect of planting densities of cv. Arbequina trees on olive oil quality and composition was studied along the first four years of production. Two types of planting tree arrangements were evaluated, namely olive trees planted at different distances within a row (2.0 m; 1.5 m; 1.25 m; and 1.0 m, fixing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
22
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 39 publications
6
22
0
1
Order By: Relevance
“…These values are significantly higher than those of most vegetable oils, e.g. canola oil (0.36), olive oil (0.08-0.12), soybean oil (0.15), Safflower (0.01) Atlas pistachio (0.10) and walnut oil (0.25) (Galão et al, 2014;Ojeda-Amador et al, 2018;Rodrigues et al, 2018;Beyzi et al, 2019;Labdelli et al, 2019;Roche et al, 2019). The tocopherol content increased in same way between 17 to 24 DAF (Tab.…”
Section: Fatty Acid Compositionmentioning
confidence: 82%
“…These values are significantly higher than those of most vegetable oils, e.g. canola oil (0.36), olive oil (0.08-0.12), soybean oil (0.15), Safflower (0.01) Atlas pistachio (0.10) and walnut oil (0.25) (Galão et al, 2014;Ojeda-Amador et al, 2018;Rodrigues et al, 2018;Beyzi et al, 2019;Labdelli et al, 2019;Roche et al, 2019). The tocopherol content increased in same way between 17 to 24 DAF (Tab.…”
Section: Fatty Acid Compositionmentioning
confidence: 82%
“…Vitamin E content was obtained by adding the individual tocopherol contents (α-, βand γ-), which were determined according to the ISO 9936 (2006), with some modifications (Rodrigues, Casal et al, 2018). Tocopherols standards and the internal standard 2-methyl-2-(4,8,12trimethyltridecyl)chroman-6-ol (tocol) were respectively from Sigma (Spain) and Matreya Inc. (USA).…”
Section: Vitamin E Contentmentioning
confidence: 99%
“…In case of VOO and EVOO, about 95% of them come from the mesocarp (fleshy mesocarp and epicarp) and only 5% come from the seed of the OF such as embryo and endosperm, after twice pressing, that is, by cold pressing without any chemicals, with small amount of heat applied (Borges, Alberto, et al, 2017; Borges, Carlos, et al, 2017). In another study, the crop year and the density of olive tree affected the chemical composition of the OO obtained from OF (Rodrigues et al., 2018). In this sense, it can be concluded that the strength of the biological effects of OO differs as a result of chemical composition.…”
Section: Commercial Classification and Chemical Contents Of Olive Oilmentioning
confidence: 99%
“…Altogether during in vitro (cell culture, gastrointestinal digestion) and in vivo (animal and human) investigation, OOP identified was sooner or later got absorbed and was available for storage and physiological events; furthermore, it was also participated in the biological functions quantitatively (Rodriguez‐Concepcion et al., 2018; Mosele et al, 2014). Nowadays, it is considered that in the absorption of lipophilic compounds, in particular, carotenoids (Rodrigues et al, 2018), they are unable to dissolve in the aqueous environment until their release from the matrix, and they need to be merged into colloidal solution. In this sense, the lipids and bile components get developed and possibly picked up by the apical surface of the enterocytes from which lipophilic compounds can be absorbed in a long run, and are further incorporated into circulation (Meléndez‐Martínez et al., 2017).…”
Section: Olive Oil Polyphenol (Oop) Bioavailabilitymentioning
confidence: 99%